Território do agronegócio : expansão dos monocultivos do eucalipto e da produção de celulose na Bahia - Oliveira, Jacson Tavares de (2014)
The expansion ofagribusiness eucalyptus in Bahia, result of global movement of reproduction of the capitaltowards to territories that are favorable to high biomass productivity,did not realize the promises of regional development and generation of employment and income,on the contrary, intensified even more conflict in capital x working in field.The implementation of the neoliberal project in the country and the economic opening were crucial for the entry of large multinational pulp and paper in Bahia,including the implementation of financial and technological alliances between competitors in the world market,but in national territory, came together to strengthen the power of competition in the global market.Under the unconditional support of the State in its different extracts government, companies materialize their projects installation of pulp mills in Camaçari, Mucuri and Eunapoliswith the formation of extensive eucalyptus plantations in the Northeast and South Baianos, becoming the largest landowners in Bahia.This thesis could be proved by reducing the number of jobs in the field and in the factories,by increased land concentration by reducing the available territory for peasant reproduction, as well as the percentage decrease social contribution of companies in the period 2005-2012. The companies benefit both through public funding and tax exemption mechanisms,as the flexible labor laws and simplification of environmental licensing.This process feeds the socio-territorial movements, notably the Movimento dos Trabalhadores Sem Terra (MST),and reveals the existence of a field in conflict analyzed in territories (Bahia Specialty Cellulose, Suzano Papel e Celulose e Veracel Celulose).The encampments and settlements surveyed in the territory Veracel portray the peasant resistance against agribusiness eucalyptus in the historical struggle for territorial,as conflict resultingfrom universal dialectical interaction between capitalXworking. This thesis shares the historical and dialectical materialism as a method of interpreting reality and recognize the territory as a product of power relations,not only within the State and dominant groups, but especially, within the dominated groups, responsible for the production of wealth andable to act as a class and build new life references andof social organization beyond the logic of capital and their presuppositions.